The transition to a new economy after the second industrial revolution - Atkeson, Andrew 1961-; Kehoe, Patrick J. (NBER working paper series, 2001)
During the Second Industrial Revolution, 1860-1900, many new technologies, including electricity, were invented. These inventions launched a transition to a new economy, a period of about 70 years of ongoing, rapid technical change. After this revolution began, however, several decades passed before measured productivity growth increased. This delay is paradoxical from the point of view of the standard growth model. Historians hypothesize that this delay was due to the slow diffusion of new technologies among manufacturing plants together with the ongoing learning in plants after the new technologies had been adopted. The slow diffusion is thought to be due to manufacturers' reluctance to abandon their accumulated expertise with old technologies, which were embodied in the design of existing plants. Motivated by these hypotheses, we build a quantitative model of technology diffusion which we use to study this transition to a new economy. We show that it implies both slow diffusion and a delay in growth similar to that in the data.